Enhancing Students’ Descriptive Writing Skills through the Picture Word Inductive Model (PWIM) - Hakimah, Nurul (English Language and Literature in Education Journal, 2024)
Research on enhancing students’ descriptive writing skills has consistently highlighted challenges, particularly the persistent gaps in performance and the limited effectiveness of conventional teaching methods. In this context, the present study addresses these issues by implementing the Picture Word Inductive Model (PWIM) at SMP Negeri 48 Surabaya during the 2020/2021 academic year. Initial data revealed a significant problem: the pre-test scores of the 42 students in class 7-B showed a mean of 62.88, with only 4.76% meeting the success criteria, underscoring the ineffectiveness of traditional approaches. Despite modest gains in the post-test scores of Cycle I, where the mean increased to 72.76 and 16.67% of students passed, the results remained inadequate. By employing Classroom Action Research (CAR) and focusing on PWIM, this study aimed to bridge the identified gaps. Observational data and testing across two cycles demonstrated significant advancements by Cycle II, with a mean post-test score of 85 and 80.95% of students meeting the success criteria, indicating a substantial improvement in descriptive text writing skills. The t-test analysis further confirmed the effectiveness of PWIM in significantly enhancing students’ writing performance. These findings suggest that PWIM not only addresses the deficiencies in students’ writing but also offers a viable strategy for broader application in similar educational contexts. The study underscores the need for future research to explore the long-term effects and applicability of PWIM across different subject areas to further validate and refine its effectiveness.